ANALISIS YURIDIS PENGUASAAN TANAH TERLANTAR EX HAK GUNA USAHA OLEH MASYARAKAT DESA KASOMALANG - Nadya, Alifa; Hernawan, Deddy (Faculty of Law, Universitas Pasundan, 2024)
The rapid development of the times and community development has caused an increase in population, but this increase in population was not in line with the availability of land. Land has a very high economic value so that it is everyone's obligation to maintain and retain its existence as an object of economic value. One type of land right is Cultivation Rights, which is the right to manage a piece of land given by the state to a business entity or individual in order to increase productivity and community welfare. This research is normative juridical research with the nature of descriptive research analysis, the data obtained is then analyzed with qualitative juridical methods. The abolition of Cultivation Rights resulted in the status of land becoming state land, so that the state reorganized its use, usage, and ownership through the Minister. If the Cultivation Rights period has expired and more than 2 (two) years the party granted by Cultivation Rights does not carry out the rights renewal process and does not cultivate and utilize the land granted, it cannot have priority rights. On the contrary, people who use land that is not cultivated or used by former rights holders, are entitled to priority rights as proposed by Ter Haar. However, the community still needs to apply for rights through the local Land Office. Keywords : Cultivation Rights, Abandoned Land, Land reform.